การวางแผนกลยุทธ์ทางการตลาดเพื่อเพิ่มยอดขายน้ำมะนาวแท้แช่แข็ง ตรา ลาลา เทศบาลนครขอนแก่น จังหวัดขอนแก่น - เฮ้งบริบูรณ์, ศิรินภา; ตัตตะวะศาสตร์, อารมย์; เจริญศิริพรกุล, ศักดิ์ชัย (MBA-KKU Journal, 2017)
การศึกษานี้ มีวัตถุประสงค์เพื่อศึกษาพฤติกรรมการใช้น้ำมะนาวในเขตเทศบาลนครขอนแก่น โดยใช้วิธีการสำรวจโดยแบบสอบถามจากผู้บริหารร้านอาหารที่มีพฤติกรรมการใช้น้ำมะนาวในเขตเทศบาลนครขอนแก่น จำนวน 160 คน ผลการศึกษา พบว่า ผู้ตอบแบบสอบถามส่วนใหญ่ใช้มะนาวสดในการปรุงอาหารส่วนใหญ่ผู้บริหารร้านเป็นคนตัดสินใจเลือกซื้อ และซื้อที่ตลาดสด ให้ความสำคัญในการเลือกซื้อจากคุณภาพ สินค้าทดแทนที่เลือกใช้ คือ น้ำมะนาวแท้แช่แข็ง ปัจจัยที่มีผลต่อการตัดสินใจเลือกซื้อน้ำมะนาวมากที่สุดในแต่ละด้าน ประกอบด้วย ด้านผลิตภัณฑ์ คือ น้ำมะนาวมีรสชาติคงที่ น้ำมะนาวมีฉลากบอกวิธีใช้ วันผลิตและวันหมดอายุอย่างชัดเจน น้ำมะนาวได้รับมาตรฐานรับรอง น้ำมะนาวไม่เสียง่าย ด้านราคา คือ ราคามีความเหมาะสมเมื่อเทียบกับคุณภาพ และปริมาณ ราคาคงที่ ด้านช่องทางการจัดจำหน่าย คือ สถานที่จำหน่ายควรอยู่ใกล้กับแหล่งซื้อวัตถุดิบอื่น ด้านการส่งเสริมการตลาด คือ ควรมีโปรโมชั่นในช่วงมะนาวราคาแพง มีบริการจัดส่งฟรี จากนั้นได้ทำการวางแผนกลยุทธ์ทางการตลาดเพื่อเพิ่มยอดขายน้ำมะนาวแท้แช่แข็ง ตรา ลาลา จำนวน 5 โครงการ ได้แก่ 1) ถึงที่ ถึงใจ 2) ลาลา ชวนชิม 3) มาซื้อที่ร้านลด 5% 4) ซื้อมาก ลดมาก แถมมาก 5) ลูกค้าคือคนพิเศษ อีกทั้งยังมีโครงการพัฒนาตลาดเพื่อจำหน่ายผลิตภัณฑ์ในจังหวัดใกล้เคียงในอนาคต Abstract The Objectives of this research were to study the consumers’ behavior and purchasing decision factors by using questionnaires with 160 restaurants’ owners and entrepreneurs which probably frequently used lime juice in Khonkaen province in order to plan marketing strategy to increase sales volume for Lala frozen lime juice. The results showed that buyers selected lime juice for restaurants as foods ingredient. Restaurant owners responded for ingredients selection, bought lime juice and lime from fresh markets, chose lime juice from quality and used frozen lime juice as replacement products. Regarding to market mix factors which influenced the decision to purchase lime juice all the factors were shown at high level, according to the opinions of sample group, as follows; Products- Assured physical quality of lime juice with taste, smell and colors, apparent labeling with manufacturing or expire date along with directions, product certification, long time storable, Price - reasonable price along with quantity and quality, stable price, Place - distributor had other products for consumers to buy, Promotion - including promotions during fresh lime increasing price period, free delivery service. Therefore, in order to increase sales volume of Lala Frozen Lime Juice the marketing strategies were 1) Direct sale representative 2) Demonstration product in target market place 3) Discount for self-picking up 4) More order, more discount, more giving away 5) Customers rewards. In the future, there were project expanding target marketing to nearby provinces.